2019
DOI: 10.1007/s42452-019-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

The study of adsorption efficiency of rice husk ash for removal of phenol from wastewater with low initial phenol concentration

Abstract: This research work aimed to assess the adsorption efficiency of rice husk ash for removal of phenol from wastewater. The authors studied the morphology and characterization of rice husk ash using SEM, FTIR, XRD and BET analyzers and carried out the batch experiments to evaluate the removal percentage of phenol with variation of pH (3-11), adsorption time (30-270 min), adsorbent dose (0.5-4.0 gm/L), phenol concentration (5-20 mg/L) and temperature (25-35 °C). It was observed that the maximum removal reached as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 29 publications
2
15
1
Order By: Relevance
“…Pseudo-first-order suggests that the adsorption process is physisorption and the adsorbent particles are homogeneous (Husein, Hassanien & Al-Hakkani, 2019). This study's result agrees with the findings reported by Mandal, Mukhopadhyay & Das (2019). Reporting pseudo-second-order supporting the adsorption processes of phenol using rice husk as adsorbent.…”
Section: Kinetic Adsorption Studysupporting
confidence: 90%
See 3 more Smart Citations
“…Pseudo-first-order suggests that the adsorption process is physisorption and the adsorbent particles are homogeneous (Husein, Hassanien & Al-Hakkani, 2019). This study's result agrees with the findings reported by Mandal, Mukhopadhyay & Das (2019). Reporting pseudo-second-order supporting the adsorption processes of phenol using rice husk as adsorbent.…”
Section: Kinetic Adsorption Studysupporting
confidence: 90%
“…The highest removal efficiency of 80% was achieved at a dose of 0.15 g of CS-SiO 2 /CaCO 3 nanocomposite and remain more or less the same up to 0.25 g. Suggesting that the removal efficiency at the onset of the adsorption processes was higher due to the more available surface area, additional adsorption sites, and then remained the same due to saturating absorbent sites following an increase in the dose (Mandal, Mukhopadhyay & Das, 2019). The RHSiO 2 and ESCaCO 3 at varying initial dosage show an increase in phenol removal efficiency.…”
Section: Factors Affecting Adsorption Behaviorsmentioning
confidence: 86%
See 2 more Smart Citations
“…We suggest that such behavior is due to the collapse of pores, as confirmed by the morphology of the adsorbents (Fig 2). The surface area of the ashes studied herein was higher than that published by Kaur et al (2020) [28], Mandal et al (2019) [34] and Srivastava et al (2006) [30], who burned rice husk at 500˚C for 30 min, rice husk at 600˚C for 4 h, and bagasse and obtained surface areas of 144.23 m 2 .g-1 , 57.5 m 2 .g-1 , and 168.4 m 2 .g-1 , respectively.…”
Section: Plos Onecontrasting
confidence: 70%